Digital Constitutionalism: In Search of a Content Governance Standard - Palladino, Nicola (My University, 2022)
This work is the output of a project funded by Facebook Research. The authors conducted their research independently and their findings were subject to external peer review. No review by Facebook Research or its associates took place. We thank the participants at the Conference ‘Constitutionalising Social Media’ (Dublin, 20–21 May 2021) for their helpful comments on an earlier draft of this chapter as well as the peer reviewers for their constructive criticism. One of the main issues of global content governance on social media relates to the definition of the rules governing online content moderation. One could think that it would be sufficient for online platforms to refer to existing human rights standards. However, a more careful analysis shows that international law only provides general principles, which do not specifically address the context of online content moderation, and that a single human rights standard does not exist. Even identical provisions and principles are interpreted by courts in different ways across the world. This is one of the reasons why, since their inception, major social media platforms have set their own rules, adopting their own peculiar language, values and parameters. Yet, this normative autonomy too has raised serious concerns. Why should private companies establish the rules governing the biggest public forum for the exchange of ideas? Is it legitimate to depart from minimal human rights standards and impose more stringent rules?
Constitutionalising Social Media
PUBLISHED